(untitled) (Delta Medical College Journal, 2014)
Stabbing is the most common method of homicide in developing countries like Bangladesh, due to poverty, over population, joblessness, political unrest, etc. The reported case is of a 27 years old man stabbed on the front of the left thigh, a relatively unusual site by a sharp pointed knife by some snatchers while sitting on a rickshaw. On medicolegal point of view the injury was homicidal in nature to run away without having a motive to kill the person. The site was easily approachable for the snatchers. We need to create awareness among general population about the circumstances and probable mishaps that can happen unexpectedly. DOI: http://dx.doi.org/10.3329/dmcj.v2i1.17795 Delta Med Col J. Jan 2014; 2(1): 36-38